2014
DOI: 10.1242/jcs.143842
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genome protective vs. ribosome synthetic functions of the paralogous nucleolar proteins nucleostemin and GNL3L

Abstract: The mammalian nucleolar proteins nucleostemin and GNL3-like (GNL3L) are encoded by paralogous genes that arose from an ancestral invertebrate gene, GNL3. Invertebrate GNL3 has been implicated in ribosome biosynthesis, as has its mammalian descendent, GNL3L. The paralogous mammalian nucleostemin protein has, instead, been implicated in cell renewal. Here, we found that depletion of nucleostemin in a human breast carcinoma cell line triggers prompt and significant DNA damage in S-phase cells without perturbing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…In a recent study from my laboratory, we observed a cell cycle arrest upon nucleostemin knockdown in human breast cancer cells (MDA-MB-231) after 12 hours, and found that, at this early time point compared with other related studies, nucleostemin depletion causes an increase in cells in S phase and a decrease of those in G2/ M, indicative of an intra-S-phase arrest (Lin et al, 2014). Most importantly, our dose-dependent study revealed that the apparent discrepancy with regard to the cell cycle effects of nucleostemin depletion among different studies might be due to the level of protein knockdown.…”
Section: The Amazing Diversity Of Cell-cycle-arrest Profiles Of Nuclementioning
confidence: 51%
See 4 more Smart Citations
“…In a recent study from my laboratory, we observed a cell cycle arrest upon nucleostemin knockdown in human breast cancer cells (MDA-MB-231) after 12 hours, and found that, at this early time point compared with other related studies, nucleostemin depletion causes an increase in cells in S phase and a decrease of those in G2/ M, indicative of an intra-S-phase arrest (Lin et al, 2014). Most importantly, our dose-dependent study revealed that the apparent discrepancy with regard to the cell cycle effects of nucleostemin depletion among different studies might be due to the level of protein knockdown.…”
Section: The Amazing Diversity Of Cell-cycle-arrest Profiles Of Nuclementioning
confidence: 51%
“…It is apparent that DNA damage arises at the earliest time point of measurement, that is 12 hours after the initiation of nucleostemin depletion, whereas no significant effect on rRNA synthesis or nucleolar structure can be noted up to 48 hours (Lin et al, 2014). This finding establishes that DNA damage occurs considerably before ribosomal perturbation in response to nucleostemin depletion.…”
Section: The End Does Not Always Justify the Meansmentioning
confidence: 74%
See 3 more Smart Citations